Beyond borders: exploring the connection between global identity and academic self-efficacy in college students – a cross-sectional study - Tarik N. Mohamed (Psychology, Society & Education)
While increasing attention has been given to the role of identity in academic outcomes, limited empirical research has explored how a global identity relates to academic self-efficacy among college students. Therefore, this study examined the association of global identity on academic self-efficacy and its relationship with academic performance among undergraduate students in Saudi Arabia. Using a cross-sectional design, data were collected from 946 students (39.5% female; M = 20.8 years, SD = 1.3) through standardized measures of global identity and academic self-efficacy. Results showed that cultural openness (i.e. global identity component) was positively associated with all dimensions of academic self-efficacy, whereas non-nationalism showed negative associations. Perceived control emerged as a significant mediator between both global identity components (i.e., cultural openness and non-nationalism) and academic performance as measured by Grand Point Average. Additionally, gender did not moderate the effect of cultural openness. In contrast, gender moderate the relationship between non-nationalism and perceived control, which was more pronounced in females. These findings highlight the complex role of global identity in academic contexts and suggest that fostering global perspectives –while supporting students’ academic confidence– may enhance academic success.